PENGEMBANGAN MEDIA PETA TIMBUL KENAMPAKAN ALAM IPS BAGI SISWA TUNANETRA KELAS VI SDLB - Faiz Muzakki; Endro Wahyuno (Universitas Negeri Malang, 2014)
The Development of Embossed Map Media Subject for Students with visual impairment 6th Grade in Elementary School of Special Needs Education. This study used Research and Development which adapted from Sugiyono’s model that been modified to be 8 steps. The score of Validation result from material expert was of 90%, from material media was of 81%, and from practitional was of 80%. With 90% can be expressed very decent, 81% was very decent stated, and 80% stated very decent. Effectiveness result of media based on student learning outcome obtained very effective criteria for 100%.Key Word: Development, Embossed Map Learning Media, Social Science, Visual Impairment Pengembangan Media Peta Timbul Kenampakan Alam IPS bagi siswa tunanetra Kelas VI di SDLB.Tujuan peneitian ini untuk menghasilkan media pembelajaran peta timbul untuk siswa tunanetra. Jenis Research and Development dengan mengadaptasi model dari Sugiyono yang telah dimodifikasi menjadi 8 langkah. Hasil validasi ahli materi, media, dan praktisi mendapatkan kriteria dengan skor 90%, 81%, dan 80%. Dengan 90% bisa dinyatakan sangat layak, 81 % dinyatakan sangat layak, dan 80 % dinyatakan sangat layak. Hasil keefektifan media berdasarkan hasil belajar siswa mendapatkan skor 100% bisa dinyatakan sangat layak.